Examining the mechanical properties of hybrid curauá-basalt reinforced polyester composites - Krishnasamy, Senthilkumar; Irulappasamy, Siva; Thiagamani, Senthil Muthu Kumar; Ilyas, R. A.; Khoo, Pui San (John Wiley and Sons, 2025)
A significant challenge in the development of natural fiber-reinforced composites is optimizing the fiber length and loading to achieve desirable mechanical properties for practical applications. Although many experimental studies have been reported on individual fiber reinforcements, limited research has explored the synergistic interplay between curauá (C) and basalt fibers (B) in polyester matrix composites. This study addresses this research gap by examining the optimal combination of these two fibers at specific fiber lengths and fiber loadings to enhance the composite performance. The novelty of this work lies in examining the interplay effects by varying the fiber lengths (4 mm, 8 mm, and 12 mm) and fiber loadings (25%, 50%, and 75%) and analyzing their effects on mechanical properties. ANOVA was also used to understand the interplay effects. The pure curauá, pure basalt, and their hybrid combinations were fabricated using a compression molding machine. The total fiber loading of basalt and curauá fibers varied in ratios of 100:0, 75:25, 50:50, 25:75, and 0:100. The results showed that the hybrid composites with 8 mm fiber lengths, consisting of 75:25 (B:C) exhibited higher tensile strength of 34.34 MPa and flexural strength of 119.6 MPa. Regarding impact strength, 8 mm fiber lengths with 25:75 (B:C) exhibited an improved value of 60.12 kJ/m2. Highlights: An 8 mm fiber length is optimal for hybridizing basalt and curauá fibers. 25% basalt and 75% curauá achieved an impact strength of 60.12 kJ/m2. ANOVA was applied to examine the interplay effect of fiber length and loading. SEM analysis revealed the morphological characteristics of hybrid composites. Curauá/basalt hybrid composites are suitable for automotive applications.